A balancing act: a grounded theory study of the professional judgement of child protection social workers. Issue 2 (3rd April 2018) - Kettle, Martin
ABSTRACT: This paper explores professional judgement of social workers working to protect children. Based on 22 in-depth interviews with social workers, a grounded theory methodology is adopted. The policy context for child protection practice is outlined and analysed. This study then explores how information, responsibility and in particular anxiety, are transacted between social workers and other professionals. Additionally, this study explores the delicate balances social workers are required to negotiate, focussing on two elements of the findings, 'closeness- distance' and 'power over- power together'. The delicacy of the balances negotiated by social workers leads to a powerful analogy of social workers as tightrope walkers, and strategies to seek balance are identified. The implications for practice are explored. The internal mental processes of social workers require closer attention, a cautious approach should be taken to rational-technical solutions and social workers should be better prepared to respectfully challenge other professionals.